Political Culture and Voting Behavior; A Case Study of Parsi Community in Pakistan - Zainab Asif Dar; Asma Awan (Journal of Political Studies, 2019)
Parsi community of Pakistan is known for great contribution in the public welfare works, literature, industry and philanthropy. Moreover Parsis are considered one of the most hardworking and peaceful communities of Pakistan. However, the population of Parsi community in Pakistan is declining rapidly due to the migration of Parsis from Pakistan to Western countries. The following paper investigates how Parsi community perceives the political and security scenario of Pakistan. This research paper will also investigate whether Parsi community has adequate political rights or not and how are they contributing and participating in the political process in Pakistan. This research paper will also inquire if Parsi community has any political grievances in Pakistan. All these questions will be answered by studying the political culture and voting behavior of Parsi community in Pakistan. Survey method of research was used to conduct the research and data was collected through a structured questionnaire. The results show that the Parsis are patriot Pakistani people but have reservations regarding the constitutional provisions on minority rights and seek a reform in the system and better law and order situation.